Physical, structural, optical and thermal investigations of TeO2-modified borate glass for solid-state devices - A. Khan; L. Shah; M. Arsalan; Ataullah; I. Khan; M. Shoaib; S.A. Khattak; Tanveer Ahmad; P.M. Ismail; G. Rooh; I. Ullah (Results in Physics)
The impact of varying TeO2 content (0, 10, and 20 mol%) on the physical, optical, structural, and thermal properties was investigated for Eu2O3 doped borate glasses. Physical parameters such as sample density, molar volume, and ion concentration confirm the structural changes resulting from TeO2 doping. The optical band gap, calculated from absorption spectra using Tauc’s plot, indicates the presence of localized states between the valence and conduction bands. X-ray diffraction (XRD) analyses confirm that the samples exhibit glass characteristics. FTIR studies demonstrate effective Te-O-Te linkages. The thermal properties, were assessed using differential thermal analysis (DTA), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). The DSC analysis revealed a computed △T of approximately 200 °C, indicating good thermal stability for the CNEBT glass. The crystallization onset and peak crystallization temperatures were observed to increase with the addition of TeO2. The reduced glass transition temperature (Trg) values suggest that internal crystallization is suppressed. TGA analysis confirmed weight loss attributed to the release of trapped solvents. The findings suggest that these glasses are suitable for use in high-temperature solid-state devices.